Explaining ISIS : differences and misconception of jihad and qital - Umi Nur Zahidah Mohd Kaslan,; Teh, Benny Cheng Guan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Jihad has long been at the center of debate on the validity of actions carried out by religion-based radical groups like the Islamic State of Iraq and Syria (ISIS) in justifying their acts of using out-of-context Al-Quran verses and Prophet Muhammad sayings to equate the ancient war times with present day situation in order to create and develop a heavily misled idea of a caliphate. This radicalization arguably contributes to the growing xenophobic sentiments toward Islam and its followers through generalization made by diverse parties especially Islamophobes. To unpack the hugely contested notion of jihad and its use by ISIS, this study examines the differences between jihad and the concept of qital. The non-war view of jihad is then presented through discussions of alternative interpretations of jihad in Quranic verses and the hadiths to exemplify the wide understanding and clarification of jihad. The paper employs a qualitative approach in order to analyze non-quantifiable variables that would include God’s decree and sayings of the Prophet. It further incorporates the role of important figures and their thoughts in ultimately shaping warlike ideas of jihad that are outdated and disproportional to the current settings of the world. It finds that extremist groups have been greatly influenced by the skewed thoughts of radical thinkers and eventually resulted in the negative connotations of jihad. Such connotations are arguably far from the relevancy of the verses and hadiths that are timely-appropriate if interpreted correctly. Jihad in contemporary understanding does not only apply to a person’s own struggles for his or her own betterment but also for the advancement of the entire community in a non-aggressive manner.